2016
DOI: 10.1021/acs.jced.6b00256
|View full text |Cite
|
Sign up to set email alerts
|

Storage of Methane in Clathrate Hydrates: Monte Carlo Simulations of sI Hydrates and Comparison with Experimental Measurements

Abstract: Extensive grand canonical Monte Carlo simulations are performed for the calculation of the amount of methane gas that can be stored inside the hydrate structure sI focusing on temperature and pressure conditions that are of interest to practical applications (e.g., methane storage/transportation, methane hydrates in nature). Langmuir-type “absorption isotherms” are used in order to present the results for methane in the cages of the hydrate structure. In particular, the methane content inside the different typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 84 publications
2
17
0
Order By: Relevance
“…This will enable us to assess the agreement between simulations and experiments for a wide range of conditions covering both single and multiple occupancy regimes for the cages and to help interpret the recently measured occupancy ratios in terms of separate occupancies θ L and θ S . Notice that similar comparisons but for the simpler methane clathrate, which forms in structure I and which does not show any multiple occupancy of cages, have been performed by several authors. …”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…This will enable us to assess the agreement between simulations and experiments for a wide range of conditions covering both single and multiple occupancy regimes for the cages and to help interpret the recently measured occupancy ratios in terms of separate occupancies θ L and θ S . Notice that similar comparisons but for the simpler methane clathrate, which forms in structure I and which does not show any multiple occupancy of cages, have been performed by several authors. …”
Section: Introductionsupporting
confidence: 52%
“…Notice that similar comparisons but for the simpler methane clathrate, which forms in structure I and which does not show any multiple occupancy of cages, have been done by several authors. [14][15][16] Only few simulations results for a N 2 clathrate can be found in the literature. [17][18][19][20][21][22] Horikawa et al, and later van Klaveren et al, have studied the dynamical behavior of encaged N 2 molecules using molecular dynamics (MD).…”
Section: Introductionmentioning
confidence: 99%
“…β is equal to unity if the system follows the standard model. Moreover, the fractional occupancy calculated in this work is equal to the reported values 33,[40][41][42][46][47][48][49][50][51][52][53]89,92,93 when only single occupancy occurs (m i = 1) but can help explicitly identify multiple occupancies in a clathrate hydrate system (m i ≠ 1). In the vdWP theory, the θ ij value is calculated by the temperature-dependent Langmuir constant C ij of gas component j within type-i cage and the fugacity f j of gas component j in the hydrate phase (or gas phase).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, a number of gas hydrates have been theoretically studied by GCMC simulations in recent years, including CH 4 , CO 2 , , CO, H 2 , , N 2 , NH 3 , Ne, Ar, and Xe . For example, Lasich et al and Henley and Lucia claimed that the CH 4 molecules have almost no preference between SCs and LCs in sI hydrates, and the adsorption of CH 4 in sI hydrates can be described by a Langmuir-type adsorption model, whereas Papadimitriou et al demonstrated that the adsorption isotherm of CH 4 in sI hydrates as well as sII hydrates can be described not only by a Langmuir isotherm but also by a two-site occupancy isotherm. , Glavatskiy et al reported that the CO 2 molecules can be distinguished by two types of adsorption sites (small and large) in the sI hydrate, and the Langmuir-type adsorption model did not fit the CO 2 occupancy isotherm, but Waage et al suggested that the fractional occupancy isotherms in SCs and LCs can be described by a Langmuir-type adsorption model. Although the homogenous or heterogeneous nucleation and growth processes of the H 2 S hydrate have been explored by molecular dynamics (MD) simulations, , the molecular level information about the adsorption mechanism and spatial distribution of the impurities adsorbed in clathrate hydrates is still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, " ρ HYD " represents the ideal molar density of hydrates and was defined according to the literature [63,64]. This value was defined by assuming the ideal 100% cage occupancy, which, for the process conditions verified during experiments, can be considered acceptable (see, for instance, Papadimitriou et al, (2016) [65], where the cage occupancy was provided as a function of pressure and temperature and, at the thermodynamic conditions present inside the reactor during the process, the cage occupancy well approaches 100%).…”
Section: Methodsmentioning
confidence: 99%